Counter-Terrorism Measures: Addressing Youths Unemployment and Poverty in Northern Nigeria - Terwase, Isaac Terungwa; Mohammed Sambo, Abubakar; Mary Yvonne Atime, Shimenenge; Siben Nfor, Eric; Samuel, Falama; Onyekachi Onwuanibe, Jude; Mijinyawa, Aaron; Bala Kachalla, Lummo; Bitrus Nuhu, Mailabari; Terwase Anyam, Bartholomew (Kashere Journal of Politics and International Relations, 2023)
The Nigerian state was known for peaceful co-existence before 2009 when the Boko Haram launched attacks that bedevilled peace and security sustainability in Nigeria. The country is subdivided into six geopolitical zones which includes the North-west, North-central, North- east, South-west, South-south and South-east. Thus, Northern Nigeria comprises North-west, North-central and North-east that makes up the area of study. The study made use of qualitative research design through the conduct of interviews for the purpose of this research. The findings therefore, reveal that most of the youths who engaged in terrorism activities is as a result of unemployment and poverty in this region. It is also revealed that, some of the youths are engaged in terrorism activities so as to get a source of living. This work therefore recommends that, youths in Nigeria should be gainfully employed and fully engaged in a skill in order to eradicate terrorism in Nigeria. Also, the paper recommends industrialization in Nigeria which could serve as a tool for source of generating revenue and a source of employment opportunities for Nigerians. Thus, through establishment of industries, jobs can be created for the youths and it can generate sources of revenue for the government in order to eradicate poverty in Nigeria.